Physico-Chemical Analysis of Bore Wells Drinking Water of Nadiad Territory - Bhoi, D.K.; Raj, D.S.; Mehta, Y.M.; Chauhan, M.B.; Machhar, M.T. (Asian Journal of Chemistry, 2016)
Physico-chemical analysis such as temperature, pH, dissolved oxygen, total dissolved solids, chloride, total alkalinity, calcium and magnesium hardness, sulphate, phosphate, nitrate of bore wells water was carried out from twenty sampling stations of Nadiad territory area during February 2003–July 2003 in order to assess water quality index.